Prospective multicenter non-interventional real-world study to assess the patterns of use, effectiveness and safety of follitropin delta in routine clinical practice (the PROFILE study) - Blockeel, Christophe; Griesinger, Georg; Rago, Rocco; Larsson, Per; Sonderegger, Yum Lina Yip; Rivière, Stéphane; Laven, Joop S. E. (Frontiers in Endocrinology, 2022)
Objective To observe the real-world utilization patterns, effectiveness and safety profile of follitropin delta in women ≥18 years naïve to ovarian stimulation undergoing in vitro fertilization (IVF) or intracytoplasmic sperm injection (ICSI). Design Prospective, multinational, multicenter, observational study. All IVF/ICSI treatment protocols were conducted according to routine clinical practice, including undertaking fresh/frozen transfers. Outcomes included use of dosing algorithm, follitropin delta dosing patterns, ovarian response, pregnancy rates and adverse drug reactions (ADRs). Results The first ovarian stimulation cycle using follitropin delta was initiated in 944 women. Mean baseline demographics were: age, 33.5 ± 4.7 years; bodyweight, 67.1 ± 13.6 kg; anti-Müllerian hormone, 20.3 ± 16.1 pmol/L (2.84 ± 2.25 ng/mL). The dosing algorithm was used to calculate the follitropin delta daily starting dose in 893/944 women (94.5%). The mean difference between the calculated and prescribed daily dose was small (0.2 ± 1.40 µg). The mean daily starting follitropin delta dose was 10.4 ± 2.72 µg and the mean total dose administered was 104 µg. Follitropin delta dose adjustments were reported for 57/944 (6.0%) women. The mean number of retrieved oocytes was 10.1 ± 7.03. Ongoing pregnancy at 10–11 weeks was reported for 255 women (27.0% per initiated cycle and 43.1% per fresh transfer [n=592]). Cumulative ongoing pregnancy rate after fresh and/or frozen transfer was 36.4% (344/944). Four women discontinued follitropin delta due to ADRs. Ovarian hyperstimulation syndrome (OHSS) was the most frequently reported ADR (n=37 [3.9%]); most cases of OHSS were of mild or moderate intensity (n=30 [3.2%]). Conclusions This large real-world study of follitropin delta utilization patterns confirms its good pregnancy rates while minimizing OHSS risk during first ovarian stimulation cycle.